Suitably Incorporated Hydrophobic, Redox-Active Drug in Poly Lactic Acid-Graphene Nanoplatelet Composite Generates 3D-Printed Medicinal Patch for Electrostimulatory Therapeutics - Kumar, Sandarbh (Langmuir : the ACS journal of surfaces and colloids, 2024)
Polymer carbon composites have been reported for improved mechanical, thermal and electrical properties to provide reduced side effect by 3D printing personalized biomedical drug delivery devices. But control on homogeneity in loading and release of dopants like carbon allotropes and drugs, respectively, in the bulk and on the surface has always been a challenge. Herein, we are reporting a methodological cascade to achieve a model, customizable, 3D printed, homogeneously layered and electrically stimulatory, PLA-Graphene nanoplatelet (hl-PLGR) based drug delivery device, called 3D-est-MediPatch. The medicinal patch has been prepared by 3D-printing a Nic-hl-PLGR composite obtained by incorporating a redox active model drug, niclosamide (Nic) in hl-PLGR. The composite of Nic-hl-PLGR was characterized in three sequentially complex forms─composite film, hot melt extruded (HME) filament, and 3D printed (3DP) patches to understand the effect of filament extrusion and 3D-printing processes on Nic-hl-PLGR composite and overall drug incorporation efficiency and control. The incorporation of graphene was found to improve the homogeneity of the drug, and the hot melt extrusion improved the dispersion of drug and graphene fillers in the composite. The electroresponsive drug release from the Nic-hl-PLGR composite was found to be controllably accelerated compared to the drug release by diffusion, in simulated buffer condition. The released drug concentration was found to reach within the IC50 range for malignant melanoma cell (A375) and showed in vitro selectively, with reduced effects in noncancerous, fibroblast cells (NIH3T3). Further, the feasibility of application for this system was assessed in generating personalized 3D-est-MediPatch for skin, liver and spleen tissues in ex-vivo scenario. It showed excellent feasibility and efficacy of the 3D-est-MediPatch in controlled and personalized release of drugs during electrostimulation. Thus, a model platform, 3D-est-MediPatch, could be achieved by suitably incorporating a hydrophobic, redox-active drug (niclosamide) in poly lactic acid-graphene nanoplatelet composite for electrostimulatory therapeutics with reduced side effects